Granville Bantock's letters to William Wallace and Ernest Newman, 1893-1921 : 'our new dawn of modern music' - Bantock, Granville, Sir, 1868-1946 (The Boydell Press is an imprint of Boydell & Brewer Ltd, 2017)
Granville Bantock's letters to the Scottish composer William Wallace and the music critic Ernest Newman provide a fascinating window into British music and musical life in the early twentieth century and the 'dawn' of musical modernism.